Assessment of Mourning Process in an Anatolian City whether it is a Complicated or Cultural Grief: Case Series (Annals of Medical Research, 2021)
Aim: We aimed to analyze a case of grief ongoing for many years in women, and detected from their life and clothing style in Imranli District of Sivas. We tried to evaluate this case whether it is a complicated grief process or cultural situation which shows the fact that the social values are stressed and shows respect to the close person who died by wearing black colored cloths although the death occurred many years ago.